Flexible exchange rates - Sohmen, Egon. (Chicago : University of Chicago Press, 1969)
This book is about difference in the effectiveness of monetary policy under fixed and under flexible exchange rate with the degree of responsiveness of international capital movement to interest rate change that can now be taken for granted.
Include bibliographical footnotes and index.
oo 18/07/2018
Loans
Keywords: Foreign exchange